2023
DOI: 10.1021/acsphotonics.2c00966
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Nonlinearity and Efficient Harmonic Generation from a Strongly Coupled Light–Matter System

Abstract: Strong light–matter coupling within electromagnetic environments provides a promising path to modify and control chemical and physical processes. The origin of the enhancement of nonlinear optical processes such as second-harmonic and third-harmonic generation (SHG and THG) due to strong light–matter coupling is attributed to distinct physical effects, which questions the relevance of strong coupling in these processes. In this work, we leverage a first-principles approach to investigate the origins of the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…In the case of a longer pulse duration, we expect the SHG and FHG harmonic intensities to increase (see Appendix ). We note that with the centrosymmetry now broken (i.e., χ n ≠ 0), we can perform a frequency-dependent scan around the resonance, and we expect to obtain a similar dependence as shown in ref , where the center peak frequency of SHG and FHG is at 24.65 meV.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…In the case of a longer pulse duration, we expect the SHG and FHG harmonic intensities to increase (see Appendix ). We note that with the centrosymmetry now broken (i.e., χ n ≠ 0), we can perform a frequency-dependent scan around the resonance, and we expect to obtain a similar dependence as shown in ref , where the center peak frequency of SHG and FHG is at 24.65 meV.…”
Section: Resultssupporting
confidence: 76%
“…If the frequency of the pump field is, however, adjusted to be one-half for SHG (one-fourth for FHG), the energy of either a lower or upper polariton transition from the ground state can have efficient harmonic generation from polaritonic states, as observed in experiments 18,19,21 and theoretically predicted. 20 An added merit of coupling to a cavity mode is that we can investigate the characteristics (photon occupation and statistics) of the harmonic field generation processes, as the inversion symmetry of the system is simultaneously broken. This has been investigated for high-harmonic generation in an atomic system.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In connection with the development of quantum technologies, it could be interesting to observe the influence of the strong coupling regime on the photon entanglement in plasmonic lattices . Finally, let us note a strong-coupling-induced symmetry breaking which can boost nonlinear optical processes. , …”
Section: Plasmonic and Open Cavitiesmentioning
confidence: 99%
“…Over the past few years, the strong coupling of quantum light and matter via infrared or optical cavities has experienced a surge of interest in chemistry and materials science as a new approach for controlling or modifying chemical reactivity and physical properties. Seminal experimental work has demonstrated the possibility to control photochemical reactions , and energy transfer, , enhancement of harmonic generation from polaritonic states, modification of ground-state chemical reactions via vibrational strong coupling, , or cavity-control of condensed matter properties. , In addition, for vibrational strong-coupling (VSC), it was observed that coupling to specific vibrational excitations can inhibit, steer, and enhance molecular reaction rates. Recent theoretical investigations have focused on how light and matter become entangled and what happens to the entanglement with increasing temperature.…”
Section: Introductionmentioning
confidence: 99%